Design and implementation of an RF energy harvester at 900 MHz - Ng, Kiat Seng (2018)
This report consist of the design of a 900MHZ frequency harvester, the simulation process, as well as the implementation of the harvester circuit. The harvester consist of matching network circuits, the voltage rectifier circuit and a load, which is designed to function correlation together. The full circuit will be simulated using Advance Design System (ADS). Followed by design of the Printed Circuit Board (PCB) using eaglecad software. And finally the board will be fabricated and fully assembled with the designed components for efficiency testing. This paper uses six stages Cockcroft-Walton as the voltage rectifier which main function is to convert AC voltage to higher levels of DC output. By topology it will convert the GSM mobile signal which has a specification of 0.3Vpp 900MHz to a DC output of 1.8V. The completed circuit have been analysis with Vector Network Analyzer to observe the smith chart The project successfully harvest GSM signals and received a DC voltage of 1.2V compared to the desired result of 1.8V due to the voltage drop across the schottky diode used in the circuit.